Formic acid oxidation over hierarchical porous carbon containing PtPd catalysts - Baena Moncada, Angélica María (2013)
The use of high surface monolithic carbon as support for catalysts offers important advantage, such as elimination of the ohmic drop originated in the interparticle contact and improved mass transport by ad-hoc pore design. Moreover, the approach discussed here has the advantage that it allows the synthesis of materials having a multimodal porous size distribution, with each pore size contributing to the desired properties. On the other hand, the monolithic nature of the porous support also imposes new challenges for metal loading. In this work, the use of Hierarchical Porous Carbon (HPC) as support for PtPd nanoparticles was explored. Three hierarchical porous carbon samples (denoted as HPC-300, HPC-400 and HPC-500) with main pore size around 300, 400 and 500 nm respectively, are used as porous support. PtPd nanoparticles were loaded by impregnation and subsequent chemical reduction with NaBH4. The resulting material was characterized by EDX, XRD and conventional electrochemical techniques. The catalytic activity toward formic acid and methanol electrooxidation was evaluated by electrochemical methods, and the results compared with commercial carbon supported PtPd. The Hierarchical Porous Carbon support discussed here seems to be promising for use in DFAFC anodes.